The effect of Li+ incorporation in Yb3+-Nd3+ co-doped CaF2 phosphors over the NIR photoluminescence emission excited under visible light. Issue 4 (15th February 2021) - De Anda, J.; Huerta, E.F.; Balderas, J.U.; Righini, G.C.; Falcony, C.
Abstract: The structural and optical characteristics of Nd 3+ -Yb 3+ doped CaF2 phosphors with and without the addition of Li + ions are described in this work. The phosphors synthetized by hydrothermal and co-precipitation methods showed near-infrared (NIR) luminescence emission associated with inter-electronic transition of the Yb 3+ ion in the range of 900–1050 nm via energy transfer process from Nd 3+ ions under visible light excitation. The addition of Li + to these phosphors resulted in an improvement of the NIR luminescence intensity by a factor up to 5. The effect of the incorporation of Li + ions into the CaF2 crystallite structure, the reduction of luminescence quenching states, as well as the energy transfer mechanism involved are discussed.